The Influence of Burnout on Patient Safety Management Activities of Shift Nurses: The Mediating Effect of Compassion Satisfaction - I Seul Ryu (MDPI AG, 2021)
This study aims to investigate the levels of burnout, compassion satisfaction (CS), and patient safety management activities (PSMA) among nurses on shift work in general hospitals and to examine the mediating effect of CS on the relationship between burnout and PSMA. This was a descriptive-correlational study, conducted with a convenience sample of 301 nurses from four general hospitals. Data were collected from 1 August to 4 September 2021, using self-report questionnaires. Data were analyzed using the t-test, analysis of variance, Tukey test, Pearson’s correlation coefficient, and multiple regression analyses. Mediation analysis was performed according to the Baron and Kenny, and Sobel Tests. Significant relationships were found between shift nurses’ burnout and CS (r = −0.66, p < 0.001), burnout and PSMA (r = −0.32, p < 0.001), and PSMA and CS (r = 0.32, p < 0.001). Compassion satisfaction showed partial mediating effects on the relationship between burnout and PSMA (Z = −3.21, p = 0.001). The higher the burnout of shift-working nurses, the lower the patient safety management activity. Therefore, an effective support system at the organizational level as well as individual efforts are necessary to enhance CS and reduce burnout of shift-working nurses.